Relationships between outcome severity and attitudes towards victims of Internet love scams - Ng, Jing Wen (Nanyang Technological University, 2022)
According to the just-world theory, when people encounter innocent victims, their belief that the world is a fair place is challenged. To restore justice, many default to victim-blaming, viewing victims as responsible for their victimization. Nonetheless, some may also choose to help victims. The proliferation of Internet love scams in Singapore calls for a greater understanding of the factors influencing Singaporeans’ attitudes towards such victims. Thus, this study investigated the relationships between the severity of the financial and emotional impact of Internet love scams and people’s victim-blaming and victim-helping attitudes. 298 participants completed an online survey, where they were randomly assigned to read one of four vignettes, varying in severity of financial and emotional impact of the scam, before they rated their levels of victim-blaming and victim-helping. Results revealed higher levels of victim-blaming when the financial impact of the scam was more severe, with a small effect size (ηp2 = .037). However, higher levels of victim-blaming were not observed when the emotional impact of the scam was more severe. Surprisingly, higher severity of financial and emotional impact of the scam also generally did not lower people’s degree of victim-helping. Participants’ empathy for the victim may have potentially countered the effect of outcome severity on the degree of victim-blaming and victim-helping. These findings have implications for the development of better victim support measures.